Sustainable Development through Leadership, Servant Leadership Influence on Commitment Role for Competitive Advantage in Education - Abbas, Ansar; Saud, Muhammad; Ekowati, Dian; Usman, Indrianawati (International Journal of Psychosocial Rehabilitation, 2020)
The Leadership phenomena discussed in literature continuously to understand motivation and manifests that impact organizational development. The link of organizational development to environmental management has been negated [1], which is important to make the environment friendly/green and gain competitive advantage for sustainable development in organizational behaviour studies. Such as, improvements for positive benefits for now and future, there is a need to develop deep learning about sustainable educational leadership, [2]. Therefore, leadership and its effects in organizational settings remained the topic of scholarly discussions for decades. Leadership addresses positive psychology, attributes of a person as influencing factors in organizational life particularly towards their job commitment. The current study discussed the servant leadership and its multi-dimensional factors helping to increase commitment in employees. Through literature review, a casual model has been developed, results revealed that all components of servant leadership remain significant and increase organizational commitment to gain competitive advantage in development organizations.